Effect of a diet enriched with sodium propionate on growth performance, antioxidant property, innate-adaptive immune response, and growth-related genes expression in critically endangered beluga sturgeon (Huso huso). Issue 125 (June 2022) - Ahmadifar, Ehsan; Eslami, Mahboubeh; Kalhor, Naser; Zaretabar, Amine; Mohammadzadeh, Sedigheh; Shahriari Moghadam, Mohsen; Yousefi, Morteza; Ahmadifar, Mehdi; Hoseinifar, Seyed Hossein; Pusadee, Tonapha; van Doan, Hien
Abstract: Organic acids are active substances required for improving the productivity and wellbeing of aquatic animals. Herein, the study investigated the effects of sodium propionate on growth performance, antioxidative and immune responses, and growth-related genes expression in beluga sturgeon ( Huso huso ). For eight weeks, fish fed sodium propionate at 0, 1.2, 2.5, and 5 g kg −1 . The final weight, weight gain, and SGR were substantially increased while FCR decreased by dietary sodium propionate at 2.5 and 5 g kg −1 ( P < 0.05). The expression of Growth hormone (GH) and insulin-like growth factor 1 (IGF-1) was markedly upregulated ( P < 0.05) by dietary sodium propionate in the gills and livers of beluga. The highest mRNA level of GH and IGF-1 has been observed in fish fed a 2.5 g sodium propionate/kg diet. The red blood cells count, and hemoglobin level were meaningfully increased ( P < 0.05) by 2.5 and 5 g sodium propionate/kg diet compared with 0 and 1.2 g kg −1 levels. Further, the hematocrit level was increased ( P < 0.05) by a dietary 5 g sodium propionate/kg diet. The total protein level and lysozyme activity were meaningfully increased ( P < 0.05) by 2.5 and 5 g sodium propionate/kg diet compared with 0 and 1.2 g kg −1 levels. The highest superoxide dismutase was observed in fish fed 2.5 g sodium propionate/kg diet. Catalase activity was significantly higher in fish fed 5 g kg −1 than 1.2 g kg −1 . The glutathione peroxidase activity was markedly higher in fish fed 2.5, and 5 g kg −1 than fish fed control diet. The lowest malondialdehyde levels were observed in fish fed 1.2, and 2.5 g sodium propionate/kg diets. Moreover, the highest mucosal total protein, total immunoglobulin and lysozyme were recorded in fish fed 2.5, and 5 g sodium propionate/kg diets. The obtained results indicate that dietary sodium propionate is recommended at 2.5–5 g kg −1 to improve beluga sturgeon's growth performance, feed utilization, and wellbeing. Highlights: Dietary sodium propionate increased the growth performance of beluga sturgeon ( Huso huso ). Sodium propionate inclusion improved humoral and skin mucus immune parameters. Dietary sodium propionate supplementation exhibited the enhanced antioxidant potential of beluga sturgeon. Up-regulation of liver and gills GH and IGF-1 genes was observed in fish fed diets containing sodium propionate.